Preparation and Molecular Docking of Some Heterocyclic Compounds Containing Nitrogen and Oxygen Atoms (Lembaga Pengembangan Kinerja Dosen, 2026)
Derivatives of substituted oxazol-5-one (1–3) and substituted oxazolo-isoxazole (4–6) were successfully synthesized through a multi-step reaction process. Initially, glycine was reacted with acetic anhydride to produce acetyl glycine as a key intermediate. This intermediate subsequently underwent a condensation reaction with various substituted benzaldehydes, leading to the formation of oxazol-5-one derivatives (1–3). In the final synthetic step, these oxazol-5-one derivatives were reacted with hydroxylamine hydrochloride to yield the corresponding oxazolo-isoxazole compounds (4–6). The chemical structures of all synthesized compounds were characterized and confirmed using Fourier Transform Infrared (FT-IR) spectroscopy and proton nuclear magnetic resonance (¹H NMR) spectroscopy. Furthermore, molecular docking studies were carried out to evaluate the potential biological interactions of the prepared compounds. Docking simulations were performed using PyRx software, while visualization and interaction analysis were conducted employing PyMOL and Discovery Studio. The combined experimental and computational approaches provide valuable insights into the structural properties and potential biological relevance of the synthesized compounds.